Genesis of the institution of environmental rights of citizens in modern Ukrainian legal doctrine: natural law approach - Анісімова, Г. В. (НДІ ПЗІР НАПрН України, 2017)
The article analyses the issue of establishment and formation of the institution of citizens’ environmental rights in modern Ukrainian legal doctrine and legislation taking into consideration natural law approaches; substantiates their determinant, high priority role in the general framework of human rights. It is emphasized that the foundation of construction and the vital principle of environmental law doctrine is a systemic relationship of environmental rights and liabilities including natural rights and liabilities. Natural environmental rights are considered to be a guideline value for adapting environmental legislation of Ukraine to the relevant European and world standards.
Генезис інституту екологічних прав громадян в сучасній українській юридичній доктрині: природно-правовий підхід
Keywords: state environmental policy; natural law doctrine; environmental law doctrine; environmental legislation; environmental rights of the individual and citizens; natural environmental rights; environmental liabilities; державна екологічна політика; доктрина природного права; природоохоронне право; екологічне законодавство; екологічні права особистості та громадян; природні екологічні права; екологічні зобов'язання